Factors associated with the uptake of Covid-19 vaccines: A cross-sectional study among the students of Bishop Stuart University in South-western Uganda. - Mary Jesenta Ngabirano; Francis Kazibwe; Ronald Bahati; Bright Laban Waswa; Wycliffe Tumwesigye (Student's Journal of Health Research, 2022)
Background:  Numerous vaccines against coronavirus disease (COVID-19) were approved and distributed globally. However, little information was available on the factors that affect the uptake of COVID-19 vaccines in Uganda. The aim of this study is to find out the Factors associated with the uptake of COVID-19 vaccines among the Students of Bishop Stuart University, Mbarara City. Methodology:  A cross-sectional study design using qualitative and quantitative approaches was employed. Data was collected from a sample of randomly selected 370 respondents from Bishop Stuart University. Qualitative and Quantitative data collection methods were employed. Data was collected between 11th July and 3rd October 2022. Statistical Package for Social Sciences version 26 was used during the analysis. Chi-square and logistic regressions were used to assess factors associated with the uptake of COVID-19 vaccines. Factors with p-values <0.2 at bivariate analysis were entered into multivariate analysis. Factors with p<0.05 were considered significant. Results:  Respondents that reported always being busy with domestic work indicated a lower likelihood for the uptake of Covid-19 vaccines (AOR = 0.6, 95%CI: 0.40-0.99, p = 0.045). Respondents who perceived that the costs in the hospital were too high to manage Covid-19 illness indicated a higher likelihood for uptake of Covid-19 vaccines (AOR = 3.4, 95%CI: 1.93-6.12, p <0.001). Conclusion:  Domestic work has been found to hinder the majority of the respondents from vaccinating against Covid-19. High rates of the uptake of Covid-19 vaccines were registered among those who feared the high costs of Covid-19 illness management in hospitals. The cultural norms associated with being a male or female had impacted the decision to take Covid-19 vaccines.  Recommendation:  Community outreaches should be organized to sensitize communities about the dangers of domestic work and how to strike a balance when it comes to daily activities.